(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2015)
We describe the treatment of an adolescent girl, age 13 years old, with Class III malocclusion withnmultiple unerupted teeth in both jaw & retained deciduous teeth. Treatment consists mainly of correction of anterior crossbite, extraction of deciduous teeth, surgical exposure of unerupted teeth &orthodontic traction to help eruption, leveling and alignment with Edgewise fixed appliances with multiloop technique. Treatment time required 3years. However the treatment resulted in Class I molar occlusion with proper alignment of upper & lower anterior segment, an ideal overjet, overbite andincisor angulations. Ban J Orthod & Dentofac Orthop, April 2013; Vol-3, No.2